LMO7 Is a Negative Feedback Regulator of Transforming Growth Factor β Signaling and Fibrosis. Issue 5 (29th January 2019) - Xie, Yi; Ostriker, Allison C.; Jin, Yu; Hu, Haidi; Sizer, Ashley J.; Peng, Gang; Morris, Aaron H.; Ryu, Changwan; Herzog, Erica L.; Kyriakides, Themis; Zhao, Hongyu; Dardik, Alan; et al.
Abstract : Background: Vascular smooth muscle cells (SMCs) synthesize extracellular matrix (ECM) that contributes to tissue remodeling after revascularization interventions. The cytokine transforming growth factor β (TGF-β) is induced on tissue injury and regulates tissue remodeling and wound healing, but dysregulated signaling results in excess ECM deposition and fibrosis. The LIM (Lin11, Isl-1 & Mec-3) domain protein LIM domain only 7 (LMO7) is a TGF-β1 target gene in hepatoma cells, but its role in vascular physiology and fibrosis is unknown. Methods: We use carotid ligation and femoral artery denudation models in mice with global or inducible smooth muscle–specific deletion of LMO7, and knockout, knockdown, overexpression, and mutagenesis approaches in mouse and human SMC, and human arteriovenous fistula and cardiac allograft vasculopathy samples to assess the role of LMO7 in neointima and fibrosis. Results: We demonstrate that LMO7 is induced postinjury and by TGF-β in SMC in vitro. Global or SMC-specific LMO7 deletion enhanced neointimal formation, TGF-β signaling, ECM deposition, and proliferation in vascular injury models. LMO7 loss of function in human and mouse SMC enhanced ECM protein expression at baseline and after TGF-β treatment. TGF-β neutralization or receptor antagonism prevented the exacerbated neointimal formation and ECM synthesis conferred by loss of LMO7. Notably, loss of LMO7 coordinately amplified TGF-β signaling by inducing expression of Tgfb1 mRNA, TGF-β protein, αv and β3 integrins that promote activation of latent TGF-β, and downstream effectors SMAD3 phosphorylation and connective tissue growth factor. Mechanistically, the LMO7 LIM domain interacts with activator protein 1 transcription factor subunits c-FOS and c-JUN and promotes their ubiquitination and degradation, disrupting activator protein 1–dependent TGF-β autoinduction. Importantly, preliminary studies suggest that LMO7 is upregulated in human intimal hyperplastic arteriovenous fistula and cardiac allograft vasculopathy samples, and inversely correlates with SMAD3 phosphorylation in cardiac allograft vasculopathy. Conclusions: LMO7 is induced by TGF-β and serves to limit vascular fibrotic responses through negative feedback regulation of the TGF-β pathway. This mechanism has important implications for intimal hyperplasia, wound healing, and fibrotic diseases. Abstract : Supplemental Digital Content is available in the text.